Too many men, too-short lives: The effect of the male-biased sex ratio on mortality - Chang, Simon; Kan, Kamhon; Zhang, Xiaobo (University of Wisconsin Press, 2024)
Using a natural experiment in Taiwan, this paper shows that, for men, exposure to male-biased sex ratios at a marriageable age is associated with a greater likelihood of death in later life. In the late 1940s, over half a million soldiers from mainland China retreated to Taiwan after a civil war and were initially subjected to a marriage ban. When the ban was lifted in 1959, the great influx of mostly male soldiers into the marriage market suddenly tipped the balance in favor of women. We have found that men subjected to this massive marriage market squeeze exhibited higher mortality rates at ages 50-64. We offer several possible explanations. Surprisingly, an elevated mortality rate, albeit of a much smaller magnitude, was also observed among the women of the relevant age groups. We show that this is likely driven by the widowhood effect—women’s mortality rate increased after their husbands’ deaths.